An investigation into the practices of traditional and faith healers in an urban setting in South Africa - Karl Peltzer (AOSIS, 2001)
There is a lack of knowledge on traditional and faith healer's fees, practice and attitudes towards working within the government health sector. Opsomming Daar is gebrekkige kennis oor die fooie van tradisionele en geloofsgenesers en die praktyke en houdings ten opsigte van hulle werk in die gesondheidsdepartement van die staat. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.